Occurrence of Low Value Bycatch in Trawl Fisheries off Karnataka, India - Mahesh, V.; Benakappa, S.; Dineshbabu, A. P.; Kumar Naik, A. S.; Vijaykumar, M. E.; Khavi, Muttappa (Fishery Technology, 2017)
Bottom trawling in the most effective method ofshrimp capture but highly intensive trawling adverselyaffects benthic ecology and biodiversity. Thepresent study is aimed to throw light on low valuebycatch (LVB) landings and catch composition oftrawl boats, at Mangaluru fisheries harbour. Thequantity of fish landings by single day trawlers(SDT) during 2012-14 was 2 151.3 t y-1, of which61.8% was considered as edible grade and 38.2%was LVB. Multiday trawlers (MDT) landed anestimated 165917.2 t of fishes/yr, out of which 79.6%were marked for edible use and remaining 20.4%was landed as LVB. LVB to target group ratio forSDT and MDT landings was 1:1.66 and 1:3.93,respectively. The LVB of MDT consisted of 121finfishes belonging to 82 genera, 55 families and 13orders. An estimated 47.53% of the finfish LVBlanding by weight (56.1% by number) was contributedby juveniles of commercially important speciesand the estimated resource loss was 14044 t byweight and 11000 million in number. From thefishery resource conservation and sustainabilitypoint of view, the magnitude of resource damagedue to trawl bycatch is alarmingly increasing. Thestudy recommends using trawl nets with 35 mmsquare mesh codend, effort reduction in criticalfishing grounds and adoption of Juvenile FishExcluder cum Shrimp Sorting Device (JFE-SSD)which minimizes juvenile fish catch.